Basal cell carcinoma and syringocystadenoma papilliferum arising in nevus sebaceous on face-a rare entity - Sunil Kumar Gupta; Vivek Gupta (Wolters Kluwer Medknow Publications, 2015)
Nevus sebaceus of Jadassohn is a congenital cutaneous hamartoma comprising of multiple skin structures. It has the potential to develop into variety of neoplasms of various epidermal adnexal origins. While multiple tumors may occasionally arise, it is unusual to develop two different types of tumor, benign and malignant, to arise simultaneously within a single sebaceus nevus. Here in, we report a case of a 27-year-old male with two neoplastic proliferations including a syringocystadenoma papilliferum a benign tumor and basal cell carcinoma a malignant tumor arising in a long-standing nevus sebaceus on the face. Neoplastic changes are common in nevus sebaceous present on scalp but our case is unique due to the presence of two different types of neoplasm in a nevus sebaceous which was present on face.